How large are the direct employment effects of new businesses? An empirical investigation - Michael Fritsch; Antje Weyh (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2004)
We analyze the development of employment in start-up cohorts, which is the direct gross employment effect of the new businesses. The data is for West Germany and covers the 1984- 2002 period. While total employment in the cohorts remains above the initial level in manufacturing, we find a pronounced decline of employment below this level in the service sector. Only a small fraction of the firms create a considerable amount of jobs. The contribution that the start-up cohorts of the 1984 - 2002 period made to total employment in 2002 is nearly three times as high in services as in manufacturing. – – Der Aufsatz untersucht die Beschäftigungsentwicklung einzelner Gründungskohorten und damit den direkten Beschäftigungseffekt der neuen Betriebe. Die Analyse bezieht sich auf Westdeutschland im Zeitraum 1984-2002. Während im Industriesektor die standardisierte Beschäftigungsentwicklung über den Beobachtungszeitraum von 18 Jahren positiv bleibt, fällt sie im Dienstleistungsbereich bereits ab dem ersten Jahr nach der Gründung fast monoton. Nur ein kleiner Teil der Betriebe schafft in wesentlichem Umfang neue Arbeitsplätze. Der Anteil der Gründungskohorten der Jahre 1984 - 2002 zu den Beschäftigten 2002 ist im Dienstleistungssektor fast dreimal so hoch wie im Industriebereich.
Keywords: D21; L10; L29; M13; 330; New firms; employment change; start-up cohorts; Unternehmensgründungen; Beschäftigungsentwicklung; Gründungskohorten; Unternehmensgründung; Beschäftigungseffekt; Schätzung; Deutschland